IMAGES-METAPHORS IN THE ORNAMENTATION OF UKRAINIAN ICONOSTASIS OF THE BAROQUE PERIOD - Olianina Svitlana (World Science, 2018)
In this paper, I adduce new evidence that the decorative program of Ukrainian iconostasis contained the images-metaphors and one of them was a coat of arms of the donor. The iconoraphic programme of the Ukrainian iconostasis, during the 17th — 18th centuries is regularly complemented by coats of arms of Hetmans, Cossack leaders and high- ranking Orthodox clergy. These images are placed in the antependium of iconostases, usually there are several coats of arms and they belong to different family members. Accommodation of the groups of coats of arms in the iconostasis, not just the coat of arms of the donor, indicates that that was the plan that can be understood only in semantic programme of iconostasis. In the system of iconic (portrait) images of the iconostasis, the coats of arms is understood as a kind of codes, that were associated to a specific person, becoming not only his distinctive sign or sign with legal meaning, but the symbol, denoting the person and functioning as his portrait. In this sense emblems formally did not conflict with other personal images in the iconostasis and could be included in its symbolical space. At the same time, by virtue of its form of emblem, the coat of arms did not become on a par with icons, so even though it was placed in the iconostasis, it was expelled from the circle of images intended for worship. In the location of coat of arms in the iconostasis can be seen soteriological expectations of the customer and his family.